Copyright Law v. Trade Policy: Understanding the Golan Battle Within the Tenth Circuit - Gard, Elizabeth Townsend (The Columbia Journal of Law & the Arts, 2011)
The Tenth Circuit seems to be in a battle with itself over the meaning and definition of our copyright system. In the last two years, the Tenth Circuit defined the public domain as a constitutionally protected component of the copyright system, and then reversing itself, defined copyright (ignoring the public domain) as a tool for international trade, where treaty obligations outweigh tradition. The Golan case stands at the center of competing priorities and definitions. How are we to understand the “physics” of the public domain within contemporary copyright law? Does copyright have principles and an internal logic to foster creativity, or is copyright to be seen as malleable tool for trade and international relations? Judge Henry in the 2007 Tenth Circuit Golan v. Gonzales stated that under the traditional contours of copyright, what comes into the public domain, stays in the public domain.4 With this came a First Amendment right to use public domain works, and he remanded the case back to the district court to further determine whether the statute in question required content-based or content-neutral First amendment analysis.5 This decision marked the first time a part of the copyright law had been found unconstitutional, and it also marked a moment where the public domain appeared to be protected by the U.S. Constitution.6 Upon appeal from the district court remanded decision, the Tenth Circuit appeals court—albeit with a different chief judge—found the same statute not in violation of the First Amendment, and perfectly in line with the United States’ treaty and international obligations.7 In this opinion, works in the public domain were fair game, particularly because their restoration would somehow help American authors indirectly.8 Copyright was merely a tool for trade law, and, because of this, any alteration was acceptable and necessary.